2021
DOI: 10.3390/s21113644
|View full text |Cite
|
Sign up to set email alerts
|

First-Principle Studies of the Vibrational Properties of Carbonates under Pressure

Abstract: Using the density functional theory with the hybrid functional B3LYP and the basis of localized orbitals of the CRYSTAL17 program code, the dependences of the wavenumbers of normal long-wave ν vibrations on the P(GPa) pressure ν(cm−1) = ν0 + (dv/dP)·P + (d2v/dP2)·P and structural parameters R(Å) (R: a, b, c, RM-O, RC-O): ν(cm−1) = ν0 + (dv/dR) − (R − R0) were calculated. Calculations were made for crystals with the structure of calcite (MgCO3, ZnCO3, CdCO3), dolomite (CaMg(CO3)2, CdMg(CO3)2, CaZn(CO3)2) and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
1
12
0
1
Order By: Relevance
“…However, B3LYP still remains the best compromise between a small number of empirical adjustable parameters (three) and a wide range of highly-accurate properties. In [ 26 , 27 ], the authors were able to calculate the vibrational properties of alkaline-earth metal carbonates.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…However, B3LYP still remains the best compromise between a small number of empirical adjustable parameters (three) and a wide range of highly-accurate properties. In [ 26 , 27 ], the authors were able to calculate the vibrational properties of alkaline-earth metal carbonates.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Расчеты проводились в обобщенно-градиентном приближении с РВЕ функционалом [21]. Использовались также градиентный функционал PBESOL [22], гибридный PBESOL0, с обменно-корреляционным функционалом [22] и 25% обменом по Хартри-Фоку, а также гибридный функционал B3LYP, который сочетает в себе 20% обмен по Хартри-Фоку с обменным функционалом BECKE [23] и корреляционным функционалом LYP [24], который ранее [25,26] хорошо зарекомендовал себя в расчетах колебательных свойств карбонатов щелочноземельных металлов. Обратное пространство дискретизируется с использованием сетки Монкхорста-Пака [27] с 216 независимыми k-точками в неприводимой части зоны Бриллюэна.…”
Section: метод расчетаunclassified
“…To overcome these challenges, much effort has been spent to find environmentally friendly and stable halide perovskites. For the substitution of Pb, several Pb-free perovskites have been discovered in the past few years. , Among these compounds, Bi- and Ag-based halide double perovskites (DPs) without Pb have been proposed and synthesized in recent years as stable and environmentally friendly alternatives. , However, these Bi- and Ag-based DPs show indirect band gaps. Indirect band gap materials are not suitable for thin-film photovoltaic applications, because an indirect band gap implies weak oscillations that cause optical absorption and radiative recombination .…”
Section: Introductionmentioning
confidence: 99%
“…As reported, high-pressure technology can be a clean tool for adjusting the lattice parameters and electronic configuration of materials and was used to change the various physical and chemical properties of materials without introducing impurities. , In recent years, conventional halide perovskites under compression have been widely studied, and various new phenomena have been reported, such as pressure-induced amorphization, metallization, band gap modulation, , and emission enhancement . However, only a few studies of halide DPs under high pressure have been reported thus far. , Using high-pressure methods to explore the structure and properties of Cs 2 AgInCl 6 DP nanocrystals can aid in gaining an atom-level understanding for a fundamental study of such materials.…”
Section: Introductionmentioning
confidence: 99%